Deep integration of power electronics in battery systems - Chatzinikolaou, E (2018)
This thesis explores the concept of Power Electronics Enhanced Battery Packs (PEEBPs) where each cell (or small groups of cells) is connected to an individual converter and can be bypassed without interrupting operation of the system. The control flexibility provided can enhance system reliability by enabling failed cells to be bypassed online and improve balancing performance by controlling the duty cycle of each cell according to their respective capacity. However, the increased amount of power electronics compared to conventional system designs can potentially increase cost and power losses, while introducing additional control challenges especially for large-scale systems including thousands of cells. This thesis introduces a linear programming framework for evaluating the balancing performance of PEEBPs that perform duty cycle balancing, compared to energy redistribution active balancing circuits. The numerical results demonstrate the superior balancing performance of PEEBPs, especially when using cells with extreme capacity variations. In order to compare battery energy storage system (BESS) designs with different levels of integration of power electronics in the battery pack, a design methodology is proposed that takes into account power losses, reliability and cost. This methodology is used to compare three competing system designs for a 1 MW/ 1 MWh BESS connected at 11 kV. The results of this case study indicate more than an order of magnitude improvement in reliability when using a PEEBP (when the failure rate of the cells is similar to that of the power electronic switches), with a relatively small increase in power losses (~2% lower efficiency for the deeply modular PEEBP considered in this study). Regarding the implementation of a PEEBP, the Cascaded H-Bridge multilevel converter (CHB) is identified as an attractive candidate due to its modular design and the ability to perform direct DC-to-AC conversion. This work presents a theoretical analysis of the operation of the CHB in a BESS application and proposes a method to achieve relative state-of-charge (RSoC) estimation by making pseudo open-circuit voltage (POCV) measurements. In order to address control complexity of large scale systems a hierarchical balancing control algorithm is proposed. In this case the system is organised in conceptual hierarchical layers and each layer is equipped with a local controller. The developed algorithm can achieve global cell balancing by balancing the objects of the intermediate layers of the system with limited information exchange between the local controllers. This hierarchical balancing algorithm is experimentally validated using a CHB-BESS comprising 144 lithium titanate cells.